2004
DOI: 10.1093/ejo/26.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial skeletal and soft tissue morphology in Icelandic adults

Abstract: The purpose of the study was to describe the craniofacial characteristics of Icelandic adults on lateral skull cephalograms. The material consisted of 155 (47.8%) males and 169 (52.5%) females. The mean ages were 35.5 and 34.2 years, respectively. Twenty-two skeletal reference points and 11 soft tissue points were digitized and processed by standard methods with the Dentofacial Planner computer software program. The 45 variables calculated were both angular and linear. Two-sample t-tests were used to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 19 publications
2
20
0
1
Order By: Relevance
“…Subjects reported no history of swallowing, neurological, craniofacial, or musculoskeletal disorders. Sex and racial differences in craniometric measures, vocal tract dimensions, and levator muscle morphology have been reported (e.g., Chung et al, 1985; Chung et al, 1986; Yuen et al, 1989; Liu et al, 2000; Simpson, 2001; Ettema et al, 2002; Johannsdottir et al, 2004; Yeong and Huggare, 2004). These reported hard tissue variations indicate that further soft tissue variations may result from using diverse races, particularly in the area of the velopharyngeal mechanism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects reported no history of swallowing, neurological, craniofacial, or musculoskeletal disorders. Sex and racial differences in craniometric measures, vocal tract dimensions, and levator muscle morphology have been reported (e.g., Chung et al, 1985; Chung et al, 1986; Yuen et al, 1989; Liu et al, 2000; Simpson, 2001; Ettema et al, 2002; Johannsdottir et al, 2004; Yeong and Huggare, 2004). These reported hard tissue variations indicate that further soft tissue variations may result from using diverse races, particularly in the area of the velopharyngeal mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…Normative data is essential to understanding the complexity of abnormal anatomy, such as that in children born with cleft palate. Numerous studies have demonstrated the impact of race, sex, and age on the bony craniofacial and velopharyngeal structures (e.g., Chung et al, 1985; Chung et al, 1986; Yuen et al, 1989; Liu et al, 2000; Simpson, 2001; Ettema et al, 2002; Johannsdottir et al, 2004; Yeong and Huggare, 2004). Because the velopharyngeal musculature is attached to these bony structures, it is reasonable to assume that significant differences exist as a function of age, race, and sex.…”
mentioning
confidence: 99%
“…Subjects reported no history of swallowing, neurological, or musculoskeletal disorders. Sex and/or racial differences in craniometric measures, vocal tract dimensions, and levator muscle morphology have been reported (Chung et al, 1985; Chung et al, 1986; Yuen et al, 1989; Liu et al, 2000; Simpson, 2001; Ettema et al, 2002; Johannsdottir et al, 2004; Yeong and Huggare, 2004). These reported hard tissue variations may result in further soft tissue variations, particularly in the area of the velopharyngeal mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…30 Debido a ello se han establecido las normas cefalométricas PA para diferentes grupos étnicos y raciales. 26,31,32 En Colombia, el mestizaje ha dificultado la identificación de estos estándares de medición.…”
Section: Discussionunclassified